PD-1/PD-L1 inhibitor-induced hyponatremia: a real-world pharmacovigilance analysis using FAERS database - Tao, Chao; Liu, Bingyao; Dai, Yan; Lv, Jinyi; He, Huanhuan; Ding, Qian; Chen, Kun; Wang, Ke; Yang, Liuxuan; Ren, Xiaoqun; Zhou, Meiling (Frontiers in Immunology, 2025)
BackgroundWith the increasing use of programmed cell death protein 1 and programmed cell death ligand 1 (PD-1/PD-L1) inhibitors in cancer treatment, hyponatremia has emerged as a notable adverse event associated with this class of drugs.MethodsWe extracted adverse event reports related to PD-1/PD-L1 inhibitor-induced hyponatremia from the FDA Adverse Event Reporting System (FAERS) database, spanning from Q1–2004 to Q2 2024. The reports were analyzed for disproportionality using four methods: reporting odds ratio, proportional reporting ratio, Bayesian confidence propagation neural network, and multi-item gamma Poisson shrinker. Signals of hyponatremia associated with nivolumab, pembrolizumab, and atezolizumab were assessed at both the Standardized MedDRA Query and preferred term levels.ResultsA total of 1,339 reports of hyponatremia involving 1,274 patients were identified, with nivolumab, pembrolizumab, or atezolizumab as the primary suspected drugs. All four methods consistently indicated positive signals for hyponatremia with these drugs. Hyponatremia induced by PD-1/PD-L1 inhibitors predominantly occurred in patients aged 45 and older, with a higher incidence in males. The median onset times were 42 days for nivolumab, 35 days for pembrolizumab, and 20 days for atezolizumab. Except for atezolizumab, the median onset times for hyponatremia induced by nivolumab and pembrolizumab differed across genders and age groups.ConclusionThis pharmacovigilance analysis reveals the association between PD-1/PD-L1 inhibitors and hyponatremia, offering valuable insights to refine treatment strategies and improve risk management for this AE.